2021
DOI: 10.1002/ctm2.310
|View full text |Cite
|
Sign up to set email alerts
|

FTO modifies the m6A level of MALAT and promotes bladder cancer progression

Abstract: Background Nearly a half million people around the world are diagnosed with bladder cancer each year, and an incomplete understanding of its pathogenicity and lack of efficient biomarkers having been discovered lead to poor clinical management of bladder cancer. Fat mass and obesity‐associated protein (FTO) is a critical player in carcinogenesis. We, here, explored the role of FTO and unraveled the mechanism of its function in bladder cancer. Methods Identification of the correlation of FTO with bladder cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 42 publications
4
86
1
Order By: Relevance
“…Wen et al found that knockdown of FTO apparently induces BC cell proliferation and migration, and the effect of cisplatin-induced cytotoxicity of BC cell is rescued via the inhibition of FTO [40]. In addition, FTO can demethylate MALAT1 which further promote BC cell viability and proliferation through the miR-384/MAL2 m 6 A axis [41]. Similarly, Song et al revealed that FTO, stabilized by USP-18 via inhibition of proteasomal degradation, reduces PYCR1 m 6 A methylation and stabilizes its transcript, which finally facilitates BC cell initiation and progression [42].…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al found that knockdown of FTO apparently induces BC cell proliferation and migration, and the effect of cisplatin-induced cytotoxicity of BC cell is rescued via the inhibition of FTO [40]. In addition, FTO can demethylate MALAT1 which further promote BC cell viability and proliferation through the miR-384/MAL2 m 6 A axis [41]. Similarly, Song et al revealed that FTO, stabilized by USP-18 via inhibition of proteasomal degradation, reduces PYCR1 m 6 A methylation and stabilizes its transcript, which finally facilitates BC cell initiation and progression [42].…”
Section: Discussionmentioning
confidence: 99%
“… 17 Due to its role in cellular metabolism, FTO has thus been considered as a promising factor involved in the pathogenesis of various cancers through inducing tumorigenesis and chemoresistance. 18 , 19 Although the expression of FTO has been found to be upregulated in NSCLC, 20 there is limited knowledge regarding the specific mechanism of FTO in NSCLC. On the basis of aforementioned evidence, we proposed a hypothesis that the FTO/E2F1/NELL2 axis may confer tumor-supporting roles in the cell behavior of NSCLC cells and thus accelerate NSCLC progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, M6A methyltransferase METTL3 is upregulated in melanoma and modulates melanoma cell invasiveness through MMP2 (Dahal et al, 2019). FTO can promote bladder cancer by regulating the miR-384, MALAT, MAL2 axis through m6A modifications (Tao et al, 2021). The IGF2BP2, LINC00460, and DHX9 complex could promote colorectal cancer proliferation and metastasis by mediating the stability of HMGA1 (Hou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%